Effect of Giving Warm Water Compresses with Red Ginger (Zingiber Officinale) on Lower Back Pain in Third-Trimester of Pregnant Women - Jesica, Fanny; Amir, Aprima Yona (Journal of Health Science and Medical Therapy, 2025)
Approximately 84% of pregnant women in the world suffer from back pain. This study aimed to determine the effect of giving warm red ginger water compresses on lower back pain in pregnant women in the third trimester in the Belimbing Health Center work area in Padang City in 2025. The research method used was quantitative with a Quasy Experiment design. Data collection was carried out from November 2024 - March 2025. The study population was all pregnant women in the third trimester in the Belimbing Health Center work area. Sampling using the purposive sampling method totaling 36 pregnant women. Data were collected using observation sheets. Data were analyzed using univariate and bivariate analysis with a dependent t-test statistical test. The study's results showed a difference in the average pain level before the red ginger warm water compress was 4.19 and after the red ginger warm water compress was 2.88. Based on the dependent t-test statistical test, it was found that red ginger warm water compresses had an effect on lower back pain in pregnant women in the third-trimester p-value = 0.000. It can be concluded that red ginger warm water compresses have an effect on lower back pain in pregnant women in the 3rd trimester in the Belimbing Health Center working area of ​​Padang City in 2024. It is hoped that the Belimbing Health Center, especially midwives, will provide one form of loving care for mothers when treating pregnant women: red ginger warm water compresses to reduce lower back pain in pregnant women.